2021
DOI: 10.3390/ijms222212580
|View full text |Cite
|
Sign up to set email alerts
|

Takinib Inhibits Inflammation in Human Rheumatoid Arthritis Synovial Fibroblasts by Targeting the Janus Kinase-Signal Transducer and Activator of Transcription 3 (JAK/STAT3) Pathway

Abstract: TGF β-activated kinase 1 (TAK1) is an important participant in inflammatory pathogenesis for diseases such as rheumatoid arthritis (RA) and gouty arthritis. The central position it occupies between the mitogen activated protein kinase (MAPK) and nuclear factor kappa B (NF-κB) pathways makes it an attractive therapeutic target. As this field has developed in recent years, several novel inhibitors have been presented as having specific activity that reduces the TAK1 function either covalently as in the case of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Although the etiology of RA remains unclear, recent evidence has suggested that activation of RA synovial fibroblasts, a complex network of cell regulation, plays a vital role in the pathogenesis of RA ( Pap et al, 2000 ; Turner and Filer, 2015 ). Thus, inhibiting RA synovial fibroblast proliferation and blocking its effects can significantly reduce RA symptoms and prevent bone destruction ( Panipinto et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of RA remains unclear, recent evidence has suggested that activation of RA synovial fibroblasts, a complex network of cell regulation, plays a vital role in the pathogenesis of RA ( Pap et al, 2000 ; Turner and Filer, 2015 ). Thus, inhibiting RA synovial fibroblast proliferation and blocking its effects can significantly reduce RA symptoms and prevent bone destruction ( Panipinto et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…8,18 Moreover, several studies have shown the benefits of STAT3 inhibition in SFs of patients with RA. [19][20][21][22] In this study, we investigated the effects of STA-21 on T cells and SFs of RA were included in the present study. The inclusion criteria were the active RA with the mentioned regimens of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…STA‐21, as a dynamic inhibitor of STAT‐3, was reported to equally modulate Th17/Treg balance, through downregulating RORγt and upregulating Foxp3 expression in CD4 + T cells, which resulted in the inhibition of autoimmune inflammation and osteoclastogenesis in an experimental trial of RA 8,18 . Moreover, several studies have shown the benefits of STAT3 inhibition in SFs of patients with RA 19–22 . In this study, we investigated the effects of STA‐21 on T cells and SFs of RA patients and evaluated how this compound can alter the autoimmune inflammation by suppressing SFs and readjusting the Th17/Treg imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…It decreases TAK1 activation by noncompetitively binding within the ATP pocket, the rate limiting step of this enzyme [ 11 ]. Additionally, in the DFG-in confirmation Takinib can competitively inhibit ATP-binding of primarily activated TAK1, causing TNFα-induced apoptosis of the synovial fibroblasts involved in rheumatoid arthritis [ 12 ]. Takinib in general has shown therapeutic applications in inflammatory and autoimmune diseases as well as different types of cancer [ 11 , 12 ], however, the protective function of Takinib in TBI remains unknown.…”
Section: Introductionmentioning
confidence: 99%